Preparation method of low-dimensional composite material for electrochemical sensing detection of nitrite

The preparation of MoO3@MoSe2 nanocomposite electrode material through hydrothermal reaction was solved, and the recognition ability and stability of electrode materials for nitrite electrochemical sensing in the prior art was achieved, and the electrochemistry with high sensitivity, specificity and long life was achieved Sensing performance.

CN119461484AInactive Publication Date: 2025-02-18TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411597441.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electrode materials for nitrite electrochemical sensing have poor specific recognition capabilities, short service life, low sensitivity, poor detection limits, and nanomaterial modified electrodes are prone to aggregation, resulting in reduced active sites and poor stability.

Method used

MoO3@MoSe2 nanocomposite electrode material is prepared through hydrothermal reaction, and selenium powder is used as a reducing agent to reduce hexavalent molybdenum in part of phosphomolybic acid to molybdenum selenide, and form a composite structure of molybdenum oxide to achieve a one-dimensional/two-dimensional structure Preparation of nanocomposite electrode materials.

Benefits of technology

High sensitivity and specific detection of nitrites are achieved, the service life of the electrode material is extended, the sensitivity and detection limit are improved, and the material has high structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461484A_ABST
    Figure CN119461484A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-dimensional composite material for electrochemical sensing detection of nitrite, and relates to the technical field of low-dimensional materials. The preparation method comprises the following steps: by taking selenium powder as a reducing agent, reducing phosphomolybdic acid under specific hydrothermal reaction conditions, and after the reaction is finished, cooling, centrifuging and drying to obtain the MoO3-coated MoSe2 nano composite electrode material. The one-dimensional / two-dimensional structure MoO3atMoSe2 nano composite electrode material prepared by the invention has the advantages of strong specific recognition capability on nitrite, long service life, high sensitivity and excellent detection limit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low-dimensional materials, and in particular to a method for preparing a low-dimensional composite material for electrochemical sensing detection of nitrite. Background Art

[0002] Nitrite (NO2 - ) is widely present in nature and plays a key role in the nitrogen cycle. It is not only an important source of nitrogen for plants to absorb, but also an intermediate product in many biological and chemical processes. As a traditional food additive, nitrite has been used for thousands of years, especially for the preservation of meat and salty foods. Its antioxidant and antibacterial properties can effectively inhibit the growth of harmful microorganisms, especially delay the production of botulinum toxin, thereby significantly extending the shelf life of food. In addition, nitrite also has certain pharmacological effects in the human body and can be used to treat certain blood-related diseases, such as improving blood circulation by promoting the production of nitric oxide. However, excessive intake of nitrite can bring serious health risks, which may lead to the formation of denatured hemoglobin and reduce the oxygen-carrying capacity of the blood. More seriously, under the action of gastric acid, nitrite can be converted into carcinogenic N-nitrosamines. This type of compound is believed to be closely related to the occurrence of many cancers, especially gastric cancer. In addition, long-term excessive intake of nitrite can also cause health problems such as high blood pressure. Therefore, although nitrite has certain benefits in food preservation and medicine, it is crucial to reasonably control its intake. Health organizations in various countries have also implemented strict monitoring to ensure the safety of public food and drinking water.

[0003] Therefore, how to effectively detect NO2 in food - The content is particularly important. Although traditional detection methods such as spectrophotometry, electrophoresis, chromatography and capillary electrophoresis are effective, they are complicated to operate and the equipment is expensive. Electrochemical sensors have gradually become the most suitable method for detecting NO2 due to their simple operation, strong real-time performance and high sensitivity. - In recent years, the performance of electrochemical sensors has been significantly improved by the composite of low-dimensional materials. For example, Bagheri et al. used MWCNT-rGO composites to modify copper nanoparticles and significantly improved NO2 - The sensitivity and selectivity of the detection were improved; Jiang et al. combined hemoglobin with graphene-AuNP composite materials to achieve NO2 - These advances indicate that electrochemical sensors can effectively detect NO2 -The application of nitrite detection has broad prospects and is expected to become a key detection tool in the field of food safety. However, the existing electrode materials for nitrite electrochemical sensing have poor specific recognition ability, short service life, low sensitivity, and poor detection limit. Among them, the electrodes modified with nanomaterials are prone to aggregation, which is the main reason for the reduction of active sites and poor stability.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a low-dimensional composite material for electrochemical sensing detection of nitrite, so as to solve the problems existing in the above-mentioned prior art and achieve highly sensitive and specific detection of nitrite.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] The present invention provides a method for preparing a MoO3@MoSe2 nanocomposite electrode material, comprising the following steps:

[0008] Selenium powder is used as a reducing agent to reduce phosphomolybdic acid through a hydrothermal reaction. After the reaction is completed, the material is cooled, centrifuged and dried to obtain the MoO3@MoSe2 nanocomposite electrode material. The temperature of the hydrothermal reaction is 200°C and the time is 16 hours. The molar ratio of the selenium powder to phosphomolybdic acid is 24:1.

[0009] Furthermore, the solvent of the hydrothermal reaction is a mixed solvent of hydrazine hydrate, ethanol and water.

[0010] Furthermore, the preparation method of the MoO3@MoSe2 nanocomposite electrode material of the present invention comprises the following steps:

[0011] (1) mixing selenium powder and hydrazine hydrate to obtain a selenium-hydrazine hydrate solution;

[0012] (2) phosphomolybdic acid is mixed with aqueous ethanol to obtain a phosphomolybdic acid solution;

[0013] (3) mixing the selenium-hydrazine hydrate solution and the phosphomolybdic acid solution, subjecting the obtained mixed solution to a hydrothermal reaction, cooling after the reaction, centrifuging, and drying to obtain the MoO3@MoSe2 nanocomposite electrode material;

[0014] The temperature of the hydrothermal reaction is 200° C. and the time is 16 h.

[0015] Furthermore, the mixing ratio of the selenium powder and hydrazine hydrate is 2mmol:5mL.

[0016] Furthermore, the volume content of ethanol in the ethanol aqueous solution is 60%; the mixing ratio of the phosphomolybdic acid and the ethanol aqueous solution is 0.083mmol:25mL.

[0017] Furthermore, the selenium-hydrazine hydrate solution is mixed with the phosphomolybdic acid solution according to a molar ratio of selenium powder to phosphomolybdic acid of 24:1.

[0018] Furthermore, the drying temperature is 60° C. and the drying time is 12 hours.

[0019] Furthermore, the stirring speed of the mixing process in step (1), step (2) and step (3) is 260 r / min, and the stirring process is at room temperature.

[0020] Furthermore, the centrifugal speed in step (3) is 7000 r / min.

[0021] In the above-mentioned preparation process of the present invention, selenium powder dissolved in hydrazine hydrate is used as a reducing agent, and a part of the hexavalent molybdenum in the phosphomolybdic acid is reduced to molybdenum selenide by controlling the reaction temperature, time and the amount of the reducing agent, and then another part of the hexavalent molybdenum self-crystallizes to form molybdenum oxide, thereby realizing the preparation of MoO3@MoSe2 composite structural material.

[0022] The present invention also provides a MoO3@MoSe2 nanocomposite electrode material prepared by the above preparation method.

[0023] The present invention further provides the use of the MoO3@MoSe2 nanocomposite electrode material as an electrochemical sensing material in detecting nitrite.

[0024] The present invention discloses the following technical effects:

[0025] The special one-dimensional / two-dimensional structure MoO3@MoSe2 nanocomposite electrode material of the present invention is beneficial to ion intercalation and dissociative adsorption in the electrochemical process, and can effectively prevent agglomeration and accumulation in the electrochemical process. The present invention combines the advantages of the electron transfer ability of ultra-thin molybdenum selenide and the sensing response of hexavalent molybdenum in molybdenum oxide to nitrite, thereby obtaining excellent electrochemical sensing nitrite performance.

[0026] The one-dimensional / two-dimensional structured MoO3@MoSe2 material of the present invention has a higher specific surface area and more active sites, has a higher structural stability, and has superior performance compared with a single MoO3 or MoSe2 material.

[0027] The one-dimensional / two-dimensional structured MoO3@MoSe2 nanocomposite electrode material prepared by the present invention has strong specific recognition ability for nitrite, long service life, high sensitivity and excellent detection limit. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is the TEM image of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0030] Figure 2 TEM image of two-dimensional MoSe2 in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0031] Figure 3 This is a high-resolution TEM image of MoO3 in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0032] Figure 4 This is the Raman spectrum analysis image of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0033] Figure 5 This is the full spectrum analysis image of the X-ray photoelectron spectroscopy of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0034] Figure 6 This is the X-ray photoelectron spectroscopy fine spectrum analysis image of the Mo element in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0035] Figure 7 In the figure, a is the electrochemical differential pulse voltammetry (DPV) test analysis diagram of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1; b, c, and d are the DPV current responses of the MoO3@MoSe2 nanocomposite electrode material, pure MoSe2 electrode material, and pure MoO3 electrode material in 0 mM nitrite and 1 mM nitrite solution environments, respectively.

[0036] Figure 8 This is the current response fitting analysis diagram of the electrochemical differential pulse voltammetry sensing of nitrite at 0.92V of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0037] Fig. 9 This is an analysis diagram of the current response at 0.92V of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1 when other interferents are added in electrochemical differential pulse voltammetry.

[0038] Fig.10 This is the current-time chronoampere curve of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1 measured at a potential of 0.92 V in a three-electrode system and BR buffer solution (pH=4). DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] Example 1

[0045] A method for preparing a low-dimensional composite material (MoO3@MoSe2 nanocomposite electrode material) for electrochemical sensing of nitrite:

[0046] (1) Preparation of selenium-hydrazine hydrate solution

[0047] Weigh 158 mg of selenium powder and 5 mL of 85% hydrazine hydrate solution, pour into a beaker for mixing, and stir with a magnetic stirrer at a speed of 260 r / min. After 30 minutes, a uniform selenium-hydrazine hydrate solution is obtained.

[0048] (2) Preparation of phosphomolybdic acid solution

[0049] Weigh 152 mg of phosphomolybdic acid, weigh 10 mL of deionized water and 15 mL of anhydrous ethanol, pour into a beaker for mixing, and stir with a magnetic stirrer at a speed of 260 r / min. After 30 minutes, a uniform phosphomolybdic acid solution is obtained.

[0050] (3) Hydrothermal reaction

[0051] 5 mL of selenium-hydrazine hydrate solution prepared in (1) was added dropwise to the phosphomolybdic acid solution prepared in (2), and stirred for 3 h at a stirring speed of 260 r / min. After stirring, the solution was transferred to a 50 mL polytetrafluoroethylene autoclave, and the autoclave was placed in an oven, the temperature was set to 200°C, and heating was continued for 16 h.

[0052] (4) Washing and drying

[0053] After cooling naturally to ambient temperature, the mixture was transferred from the polytetrafluoroethylene autoclave to a centrifuge tube and separated at a rotation speed of 7,000 r / min for 7 min. After rotation, the precipitate was washed with deionized water and collected. After repeating the process 6 times, the collected samples were placed in a vacuum oven and dried at 60 ° C for 12 h. The black reaction product finally collected is the MoO3@MoSe2 nanocomposite electrode material.

[0054] Figure 1 This is the TEM image of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0055] Figure 2 TEM image of two-dimensional MoSe2 in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0056] Figure 3 This is a high-resolution TEM image of MoO3 in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0057] pass Figure 1 and Figure 2 TEM test characterization shows the strip structure of MoO3 and the two-dimensional ultra-thin structure of MoSe2, and the two-dimensional ultra-thin MoSe2 is loaded on the MoO3 strip structure material, effectively forming a composite material structure.

[0058] pass Figure 3 The high-resolution TEM test characterization shows the lattice fringes of MoO3. The crystal structure of MoO3 is a polycrystalline structure, mainly manifested as a lattice spacing of 2.63 nanometers and a lattice spacing of 1.6 nanometers, which correspond to the (2 2 0) crystal plane and (3 3 4) crystal plane of MoO3 crystal, respectively.

[0059] Based on the unique one-dimensional / two-dimensional structure, MoO3@MoSe2 is not only conducive to ion intercalation and dissociative adsorption in the electrochemical process, but also can effectively prevent agglomeration and accumulation in the electrochemical process. Moreover, the one-dimensional / two-dimensional composite structure of MoO3@MoSe2 can utilize the composite interface effect of the material to promote electron transfer, improve the sensing efficiency, and improve the electrochemical sensing response and electrochemical stability of the electrode material. Compared with the prior art, the present invention effectively improves the electrochemical response activity, utilization rate and stability of nitrite electrochemical sensing.

[0060] Figure 4 This is the Raman spectrum analysis image of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0061] Raman spectroscopy is a widely used analytical method for studying the molecular structure of materials. It mainly uses the Raman scattering effect to analyze the scattered spectrum with a frequency different from the incident light, thereby obtaining information about the vibration and rotation of molecules. Figure 4 Raman spectroscopy analysis of MoO3@MoSe2 nanocomposite electrode materials shows that the MoO3@MoSe2 nanocomposite electrode material has the E 1g Characteristic peak (172.3cm -1 ), Characteristic peak (324.9cm -1 ) and A 1g Characteristic peak (240.4cm -1 ), and also has the characteristic peak of O-Mo-O of MoO3 (820.1cm -1 ) and the characteristic peaks of Mo-O (989.8cm -1 ), which indicates that the MoO3@MoSe2 nanocomposite electrode material was successfully prepared.

[0062] Figure 5 This is the full spectrum analysis image of the X-ray photoelectron spectroscopy of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0063] Figure 6 This is the X-ray photoelectron spectroscopy fine spectrum analysis image of the Mo element in the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0064] X-ray photoelectron spectroscopy is an effective and widely used method for testing the phase structure of materials. It is a method of using an electron spectrometer to measure the energy distribution of photoelectrons emitted from the surface of a material when irradiated with X-ray photons. Figure 5 X-ray photoelectron spectroscopy full spectrum analysis and Figure 6 The X-ray photoelectron spectroscopy fine spectrum analysis of Mo element in MoO3@MoSe2 nanocomposite electrode material shows that the test material contains characteristic peaks of Mo, Se, and O elements, and the fine spectrum shows characteristic peaks of tetravalent molybdenum (227.9eV) and hexavalent molybdenum (231.7eV), which is consistent with Figure 4 The Raman characteristic peaks of MoSe2 and MoO3 correspond to each other, which indicates that MoO3@MoSe2 nanomaterials are successfully prepared.

[0065] Figure 7 In the figure, a is the electrochemical differential pulse voltammetry (DPV) test analysis diagram of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1, b, c, and d are the DPV current responses of the MoO3@MoSe2 nanocomposite electrode material, pure MoSe2 electrode material, and pure MoO3 electrode material in 0 mM nitrite and 1 mM nitrite solution environments, respectively.

[0066] DPV has the characteristics of reducing background current, improving detection sensitivity and reducing detection limit, and can detect substances at extremely low concentrations. First, by analyzing the position and change of the peak potential in the DPV curve, the potential of the substance undergoing redox reaction on the electrode surface is determined. Then, by measuring the DPV response signal (such as peak current) of standard solutions of different concentrations, a standard curve between peak current and substance concentration is established. Figure 7 In figure a, the electrochemical differential pulse voltammetry (DPV) test of the catalytic sensing of nitrite of different concentrations by MoO3@MoSe2 nanocomposite electrode material in a three-electrode system and BR buffer solution (pH=4) is carried out. By gradually increasing the concentration of nitrite in the electrolyte (increasing by 100 μM each time, for a total of ten times) and recording the DPV response signal, it can be observed that the MoO3@MoSe2 nanocomposite electrode material has an obvious change in the current response in the three-electrode system, and it can be clearly observed that the potential position of the oxidation peak of the MoO3@MoSe2 nanocomposite electrode material for oxidative sensing of nitrite is around 0.92 V, which indicates that the MoO3@MoSe2 nanocomposite electrode material has the ability to electrochemically sense nitrite. Figure 7Figures b, c, and d are the DPV current responses of MoO3@MoSe2 nanocomposite electrode material, pure MoSe2 electrode material, and pure MoO3 electrode material in a three-electrode system and BR buffer solution (pH=4) in 0mM nitrite and 1mM nitrite solution environments, respectively. By comparing the current responses, the MoO3@MoSe2 nanocomposite electrode material has superior performance compared to the single MoO3 or MoSe2 material.

[0067] Figure 8 This is the current response fitting analysis diagram of the electrochemical differential pulse voltammetry sensing of nitrite at 0.92V of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1.

[0068] Figure 8 The corresponding is the electrochemical differential pulse voltammetry (DPV) test of the MoO3@MoSe2 nanocomposite electrode material for catalytic sensing of different concentrations of nitrite in a three-electrode system and BR buffer solution (pH = 4), recording the peak value of nitrite at the oxidation peak of 0.92V. By collecting the standard deviation of 10 blank values, the standard deviation can be obtained as 0.16458. After fitting processing by collecting three electrochemical sensing test responses, the linear relationship between the current response and the nitrite concentration is y = 12.42 + 63.05x. Through the sensitivity formula: sensitivity = slope / effective area, it can be calculated that the sensitivity of the MoO3@MoSe2 nanocomposite electrode material to nitrite sensing is 892.48μA cm -2 mM -1 . Through the signal-to-noise ratio detection limit formula: detection limit = 3 times the standard deviation of the blank value / slope, it can be calculated that the detection limit of MoO3@MoSe2 nanocomposite electrode material for nitrite sensing is 0.55μM. The sensitivity performance of MoO3@MoSe2 nanocomposite electrode material for electrochemical sensing of nitrite has a leading advantage in existing Mo-based nitrite sensors.

[0069] Fig. 9 This is an analysis diagram of the current response at 0.92V of the MoO3@MoSe2 nanocomposite electrode material prepared in Example 1 when other interferents are added in electrochemical differential pulse voltammetry.

[0070] In electrochemical sensing, specificity ensures that the sensor accurately identifies the target analyte and avoids interference from other substances. High specificity can improve the accuracy and reliability of test results, provide accurate data for disease diagnosis, environmental monitoring, etc., and has great significance for scientific research and practical applications. Fig. 9The corresponding is that after the MoO3@MoSe2 nanocomposite electrode material is subjected to electrochemical differential pulse voltammetry (DPV) test on different interferents in a three-electrode system and BR buffer solution (pH=4), the peak value of the oxidation peak at 0.92V is recorded. The present invention adds common phosphates, carbonates, nitrates, sulfites, acetates, iodine salts, chloride salts and sodium citrate in nature as interferents, and adds them at a concentration of 1mM in the same system, and records their response current at 0.92V. Fig. 9 It can be seen that the response current generated by the MoO3@MoSe2 nanocomposite electrode material and other interferents is almost negligible compared with the corresponding current generated by the MoO3@MoSe2 nanocomposite electrode material and nitrite, which indicates that the MoO3@MoSe2 nanocomposite electrode material has good specificity in the application of electrochemical sensing of nitrite.

[0071] In electrochemical sensing, the chronoamperometric technique is also an effective method for evaluating the stability of sensor electrode materials. This technique applies a constant potential on the surface of the electrode material, and by observing the degree of decay of the corresponding current response after a long test, the stability performance of the electrode material in the electrochemical sensing application is judged. In the three-electrode system and BR buffer solution (pH = 4), the present invention first changes the concentration of nitrite to 1.2mM, generating a current response of about 85μA, and then the MoO3@MoSe2 nanocomposite electrode material continues to work at a voltage of 0.92V for 3000s, and then increases the environmental solubility of nitrite in the electrolyte by 0.1mM, generating a corresponding current response of 10.09μA, and then continues to work at a voltage of 0.92V for 3000s, and then increases the environmental solubility of nitrite in the electrolyte by 0.1mM, generating a corresponding current response of 9.71μA, and its current response only loses 3.78%, indicating that the MoO3@MoSe2 nanocomposite electrode material has good electrochemical sensing nitrite durability stability, such as Fig.10 shown.

[0072] The present invention utilizes the combined advantages of one-dimensional and two-dimensional composite structures to prepare a molybdenum oxide-molybdenum selenide (MoO3@MoSe2) material with an ultrathin molybdenum selenide and one-dimensional molybdenum oxide composite structure. Based on the unique one-dimensional / two-dimensional structure, MoO3@MoSe2 is conducive to ion intercalation and dissociative adsorption in the electrochemical process, and can effectively prevent agglomeration and accumulation in the electrochemical process. Combining the advantages of the electron transfer ability of ultrathin molybdenum selenide and the sensing response of hexavalent molybdenum in molybdenum oxide to nitrite, the sensitivity of the composite electrode material for nitrite electrochemical sensing of nitrite can reach 892.48μA cm -2 mM -1, and has good detection limit, specificity and stability. The electrode material of the ultra-thin molybdenum selenide and one-dimensional molybdenum oxide composite structure synthesized by the present invention has great application prospects in electrochemical sensing detection of nitrite.

[0073] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a MoO3@MoSe2 nanocomposite electrode material, characterized in that: The following steps are involved: Using selenium powder as a reducing agent, reducing phosphomolybdic acid through a hydrothermal reaction, cooling after the reaction, centrifuging and drying to obtain the MoO3@MoSe2 nanocomposite electrode material; The temperature of the hydrothermal reaction is 200°C and the time is 16h; The molar ratio of the selenium powder to phosphomolybdic acid is 24:

1.

2. The preparation method according to claim 1, characterized in that: The solvent of the hydrothermal reaction is a mixed solvent of hydrazine hydrate, ethanol and water.

3. The preparation method according to claim 1, characterized in that: The following steps are involved: Selenium powder and hydrazine hydrate are mixed and reacted to obtain a selenium-hydrazine hydrate solution; mixing phosphomolybdic acid with an ethanol aqueous solution to obtain a phosphomolybdic acid solution; The selenium-hydrazine hydrate solution and the phosphomolybdic acid solution are mixed, and the obtained mixed solution is subjected to a hydrothermal reaction, and after the reaction is completed, the mixed solution is cooled, centrifuged, and dried to obtain the MoO3@MoSe2 nanocomposite electrode material; The temperature of the hydrothermal reaction is 200° C. and the time is 16 h.

4. The preparation method according to claim 3, characterized in that: The mixing ratio of the selenium powder and hydrazine hydrate is 2mmol:5mL.

5. The preparation method according to claim 4, characterized in that: The volume content of ethanol in the ethanol aqueous solution is 60%; the mixing ratio of the phosphomolybdic acid and the ethanol aqueous solution is 0.083mmol:25mL.

6. The preparation method according to claim 3, characterized in that: The selenium-hydrazine hydrate solution and the phosphomolybdic acid solution are mixed according to a molar ratio of selenium powder to phosphomolybdic acid of 24:

1.

7. The MoO3@MoSe2 nanocomposite electrode material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the MoO3@MoSe2 nanocomposite electrode material as claimed in claim 7 as an electrochemical sensing material in detecting nitrite.

Citation Information

Patent Citations

  • Nano MoO2-MoSe2@SFC lithium ion battery negative electrode material and preparation method therefor

    CN105428612A